Pilot study: Autologous platelet‐rich plasma used in a topical cream for facial rejuvenation. (26th July 2019) - Draelos, Zoe Diana; Rheins, Lawrence A.; Wootten, Shaun; Kellar, Robert S.; Diller, Robert B.
Abstract: Background: Platelet rich plasma (PRP) is traditionally used as an injectable material for enhanced healing, hair growth, and facial rejuvenation. Aims: This research examined the novel use of topical autologously sourced PRP added to a preservative cosmetic base and applied twice daily to the face following electroporation for 8 weeks. Methods: 20 healthy female and male subjects 30‐60 years of age were enrolled in this single‐site, investigator blinded, vehicle controlled split‐face study to evaluate the effect of a PRP‐containing serum versus the serum alone on facial photoaging. Results: 90 day stability for the PRP in a preservative serum was achieved with refrigeration at 4 degrees Celsius. Facial skin biopsy histologic findings included improved rete peg architecture. Immunohistochemical analysis showed upregulation for collagen type I with qPCR data demonstrating concomitant upregulation of mRNA for collagen after 8 weeks of topical PRP use. Conclusion: These pilot study findings may indicate value for topical PRP in facial rejuvenation.